Diversity and women's health (Baltimore : Johns Hopkins University Press, 2009)
Essays in this collection highlight the disparities in diagnosis and treatment among women because of their race, ethnicity, sexual orienta tion, disability, and age from both medical and women's studies perspec tives.
Includes bibliographical references and index.
Keywords: Minority women -- Health and hygiene -- United States; Minority women -- Medical care -- United States; Lesbians -- Health and hygiene -- United States; Lesbians -- Medical care -- United States; Older women -- Health and hygiene -- United States; Older women -- Medical care -- United States; Women with disabilities -- Health and hygiene -- United States; Women with disabilities -- Medical care -- United States; Women's health services -- United States; Cultural pluralism -- United States; Women's Health -- Collected Works; Healthcare Disparities -- Collected Works; Social justice; Women's Health -- Collected Works